Pengaruh Kejahatan Kerah Putih Terhadap Kehidupan Masyarakat - Amanda Putriasha; Citra Nabilah; Eka Faiz Rabbani; Muhammad Luthfi Wahyudi; Tugimin Supriyadi (JURNAL RISET MANAJEMEN (JURMA), 2024)
White collar crime is a serious phenomenon that has a significant impact on people's lives, both from economic, social and psychological aspects. This research aims to understand in depth the influence of white collar crime on the dynamics of community life. The methods used include analysis of related literature, case studies, in-depth interviews with perpetrators, victims and community members, as well as observations of the impact of the crime. The research results show that white collar crime can result in financial losses, damage social relationships, and trigger strong social stigma and sanctions. Apart from that, psychological impacts such as trauma, insecurity and loss of trust can also be felt by victims and society. Comprehensive prevention and treatment efforts, such as education, law enforcement and solid community development, are needed to minimize the negative effects of white collar crime.